2009
DOI: 10.15359/revmar.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Variación Espacial en Comunidades De Esponjas De La Costa Oriental De Bahía De Cochinos, Cuba

Abstract: En octubre del 2002 se estudiaron las comunidades de esponjas en cuatro localidades del arrecife de la costa este de Bahía de Cochinos, Cuba. En cada localidad se establecieron sitios de muestreo de esponjas en las zonas ecológicas de cabezos coralinos (3 m), terraza somera (6-10 m) y terraza profunda (15 m). Se utilizó el método de transecto lineal de 10 m como unidad de muestreo para medir el cubrimiento del fondo y el marco cuadrado de 1 m para estimar la densidad de la comunidad. Los índices de heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
1
5
0
11
Order By: Relevance
“…In reefs located far from significant anthropogenic disturbances, Guardia and González-Sanson (1997b), Caballero et al (2004) and Guardia et al (2006) found A. agaricites was the most abundant species. Similar results were obtained by González-Díaz et al (2003) and Caballero & Guardia (2003) in reefs under low human impact off Havana and considered these as strong reference sites for a local scale study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In reefs located far from significant anthropogenic disturbances, Guardia and González-Sanson (1997b), Caballero et al (2004) and Guardia et al (2006) found A. agaricites was the most abundant species. Similar results were obtained by González-Díaz et al (2003) and Caballero & Guardia (2003) in reefs under low human impact off Havana and considered these as strong reference sites for a local scale study.…”
Section: Discussionmentioning
confidence: 94%
“…Other research carried out in Cuban waters on healthy and unhealthy reefs do not report this species among those accounting for 95% of all identified colonies (Guardia & González-Sanson 1997a, González 1999, González-Ferrer 2000, Guardia & González-Sanson 2000b, Caballero 2002, Álvarez 2006. Several authors report this species in their studies but always in a very low percent of numerical representation (González-Díaz et al 2003, Caballero & de la Guardia 2003, Caballero et al 2004and Guardia et al 2006in Cuba, Beltran-Torres et al 2003in Mexico and Sullivan 2004. On the other hand, Steiner (1999) measured relative abundance values for this species between 5,5 to 11,4% in South Caicos in southeastern Bahamian archipelago.…”
Section: Discussionmentioning
confidence: 97%
“…En nuestro estudio, al aumentar la profundidad, generalmente se observa un incremento de la riqueza de especies, encontrándose, por tanto, los mayores valores en las estaciones situadas a 15 m. Alcolado & Herrera-Moreno (1987) y Caballero et al (2009 también registran una tendencia al incremento de la riqueza de especies con la profundidad en las comunidades de esponjas del Rincón de Guanabo y Bahía de Cochinos, respectivamente. Similar resultado obtuvieron González-Díaz (1999) y Díaz & Rützler (2001).…”
Section: Discussionunclassified
“…Según Caballero et al (2009), el sitio más expuesto de los trabajados en Bahía de Cochinos presentó la menor densidad de esponjas del estudio, posiblemente atribuida al paso de un huracán de gran intensidad en el 2001. Por otro lado, Salazar-Vallejo (2002) detectó cambios de importancia en la biomasa y densidad, mayormente de especies blandas y en digitadas erectas que se rompen desde la base tras el paso de los huracanes.…”
Section: Discussionunclassified
See 1 more Smart Citation